1999
DOI: 10.1038/sj.neo.7900066
|View full text |Cite
|
Sign up to set email alerts
|

Novel Suicide Ligands of Tubulin Arrest Cancer Cells in S-Phase

Abstract: It is presently accepted that the mechanism of action for all anti-tumor tubulin ligands involves the perturbation of microtubule dynamics during the G2/M phase of cell division and subsequent entry into apoptosis [1]. In this report, we challenge the established dogma by describing a unique mechanism of action caused by a novel series of tubulin ligands, halogenated derivatives of acetamido benzoyl ethyl ester. We have developed a suicide ligand for tubulin, which covalently attaches to the target and shows p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…Treatment of such cells with the carcinogen 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine causes early S phase arrest after short exposure times but late S-phase accumulation with longer exposure [29]. Certain tubulin ligands effect early S phase arrest in cancer cells [30].…”
Section: Protease Inhibitor Stabilizes P21 Waf1/cip1mentioning
confidence: 99%
“…Treatment of such cells with the carcinogen 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine causes early S phase arrest after short exposure times but late S-phase accumulation with longer exposure [29]. Certain tubulin ligands effect early S phase arrest in cancer cells [30].…”
Section: Protease Inhibitor Stabilizes P21 Waf1/cip1mentioning
confidence: 99%
“…Although mitotic arrest is the common mechanism for microtubule‐targeted drugs, exceptions to this have also been reported. For instance, halogenated derivatives of acetamidobenzoyl ethyl ester were found to depolymerize cellular microtubules and to arrest cells at the G 1 /S transition, indicating that antitubulin agents can inhibit cell proliferation without arresting cells at mitosis [16]. In addition, it was shown that indanocine, a microtubule‐depolymerizing agent, inhibits proliferation of certain types of noncycling tumor cell at G 0 /G 1 phase [17].…”
mentioning
confidence: 99%
“…Reports of G1 and S-phase arrest, by potent inhibitors of microtubule assembly (Davis et al, 1999;Sablina et al, 1999;Weitzel and Vandre, 2000), have been attributed to their interaction with microtubule proteins and/or spindle assembly checkpoints in different cells (Marko et al, 2002). However, by flow cytometry, cell cycle analysis of artelastin treated cells revealed an accumulation in S phase rather than a mitotic arrest.…”
Section: Discussionmentioning
confidence: 95%